Between Scholarship and Imagination: A Fictional Interpretation of the South African Writer and Social Theorist Olive Schreiner, 1855-1920. - Caulfield, Janice Leonie (Curtin University, 2022)
My creative production, 'A Woman of Passion', a novel about Olive Schreiner, South Africa's first white woman novelist and social thinker, required me to address questions raised about fictionalising a real life subject. My exegesis examines debates around Historiography, Biography and Fiction. The tension for writers of bio-fiction is between producing a novel that is trustworthy and at the same time original. My research questions address fiction's capacity for truth, and authenticity. By examining my own creative process, how I have negotiated between scholarship and imagination, I attempt to answer these questions.